Hepatic form of Dihydrolipoamide Dehydrogenase Deficiency (DLDD): phenotypic spectrum, laboratory findings, and therapeutic approaches in 52 patients - Hammann, Nicole Irene; Staufner, Christian; Schlieben, Lea Dewi; Dezsőfi-Gottl, Antal; Feichtinger, René G.; Häberle, Johannes; Junge, Norman; Konstantopoulou, Vassiliki; Kopajtich, Robert; McLin, Valérie; Rymen, Daisy; Slavetinsky, Christoph; et al. (Journal of inherited metabolic disease, 2025)
Dihydrolipoamide dehydrogenase deficiency (MIM 246900/DLDD) is an autosomal recessive mitochondrial disease with three clinical subgroups. The hepatic form leads to recurrent metabolic decompensations often accompanied by elevated levels of liver transaminases (ELT) in blood, sometimes progressing to acute liver failure (ALF). Genetically, it is linked to the p.G229C variant in the DLD gene, which has been reported in the Ashkenazi Jewish and Arabic population. In this study, we analyzed phenotypic diversity, therapeutic management, and outcome in novel symptomatic individuals with hepatic DLDD identified by whole exome sequencing (n = 7) in Central Europe as well as in previously reported cases (n = 45). Fifty-one of 52 DLDD patients carried the p.G229C variant (39 in a homozygous state). During decompensations, precipitated by febrile infectious disease or fasting, affected individuals presented with nausea, vomiting, abdominal pain, hepatomegaly, hypoglycemia, and lactic acidosis. In individuals homozygous for the p.G229C variant, neurologic manifestations were rare, whereas mild neurologic symptoms were found in individuals (n = 8) carrying a different DLD variant in trans. During decompensation, levels of specific plasma amino acids like citrulline or branched-chain amino acids, and urinary organic acids, like 2-oxoglutaric acid, were frequently elevated. However, known biomarkers—with the exception of lactate—were not consistently elevated during these episodes and typically normal in the interval, highlighting the usefulness of early genetic testing in all children with unexplained ELT or ALF to reduce the time to diagnosis. While there exists consensus for rescue therapy with intravenous glucose during decompensations and maintenance therapy with riboflavin, therapies with thiamine and antioxidants (e.g., N-acetylcysteine) were reported to be useful in single individuals with recurrent decompensations.